Calcium Phosphate Foams: Potential Scaffolds for Bone Tissue Modeling in Three Dimensions - Montufar, Edgar B; Vojtova, Lucy; Celko, Ladislav; Ginebra, Maria-Pau (Methods in molecular biology (Clifton, N.J.), 2017)
The present method describes the procedure to fabricate calcium phosphate foams with suitable open porosity, pore size, and composition to perform three-dimensional (3D) cell cultures with the objective to simulate the bone tissue microenvironment in vitro. Foams with two compositions but equivalent porosity can be fabricated. On the one hand, hydroxyapatite foams obtained by hydrolysis at 37 °C, with microstructure that mimics the small crystal size of the mineral component of bones, and on the other hand, beta tricalcium phosphate foams with polygonal grains obtained by sintering at 1100 °C. In the first part of the chapter the calcium phosphate foams are briefly described. Afterwards, the foaming process is described in detail, including alternatives to overcome processing problems than can arise. Finally, insights are provided on how to perform 3D cell cultures using the calcium phosphate foams as substrates.
Keywords: poréznost; Tissue Engineering; vyrobené materiály; fosforečnany vápenaté; Calcium Phosphates; kosti a kostní tkáň; Porosity; Particle Size; buněčné mikroprostředí; testování materiálů; Scaffold; Materials Testing; buněčné kultury; Cellular Microenvironment; Models, Biological; Hydroxyapatite; tkáňové inženýrství; krysa rodu Rattus; Animals; biologické modely; Tissue engineering; zvířata; Manufactured Materials; velikost částic; Cell Culture Techniques; Rats; Tissue Scaffolds; Bone model; Cell culture; Osteoblast; tkáňové podpůrné struktury; Three-dimensional; Tricalcium phosphate; Bone and Bones; Calcium phosphate foam